Analisis Kualitas Aplikasi Aku Pintar Dengan Menggunakan Framework ISO/IEC 25010 - Muthiah As Saidah; Henni Afra Saputri; Zulfachmi Zulfachmi (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2023)
Aku Pintar is one of the EdTech references that aims to empower the education ecosystem and improve the quality of human resources in Indonesia. Evaluation of the quality of the Aku Pintar application system is one way that needs to be done to assess and test the level of usability or functionality in identifying specific problems with the system. The measurement model that has been validated is ISO/IEC 25010 which has eight indicators covering usability, portability, performance efficiency, functional suitability, maintainability, compatibility, reliability, and security. This research was conducted using quantitative data analysis methods, validity and reliability tests using the Statistical Package for the Social Sciences (SPSS). The sample method used in this research is simple random sampling method and from slovin calculation of the number of Aku Pintar application users, the population taken is 100 respondents. The results of testing the level of application quality with the framework ISO/IEC 25010 product quality model obtained decent results with the lowest percentage, 68% for the compatibility indicator, the performance efficiency indicator was 71%, the security indicator was 74%, the reliability indicator was 75%, the maintanbility indicator 81%, then the functional suitability and usability indicators have the same percentage of 82%, then the largest percentage of portability is 91%. After obtaining the results of the percentage of the quality of the Aku Pintar application, a suggestion for improvement is made for the application so that in the future the application is better at increasing user satisfaction. . Keywords— Aku Pintar, analyze, quality, iso/iec 25010, product quality